2010
DOI: 10.1007/s10695-010-9383-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary l-tryptophan on osmotic stress tolerance in common carp, Cyprinus carpio, juveniles

Abstract: Common carp juveniles were fed two types of diet (control: 0.1% tryptophan and TRP: 0.6% tryptophan) over 15 days. Thereafter, both groups were directly subjected to osmotic challenge (from 0 to 10 ppt) for 168 h. Blood samples were collected at -240, 0, 6, 24, 72 and 168 h after challenge. Survival and serum cortisol, glucose, sodium and chloride levels were measured to determine stress response and osmoregulation condition. While TRP group showed no mortality until 168 h, cumulative mortality was near 100% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 28 publications
3
36
2
Order By: Relevance
“…Water total hardness and alkalinity were determined using portable photometers with commercial kits provided by the manufacturer (Wagtecch Portable Photometer 7100, Berkshire, UK). Cortisol was measured using LIAISON Ò cortisol assay kit (DiaSorin Inc., USA) according to Rasooli et al (2009) and Hoseini and Hosseini (2010). The procedure was competitive luminometric assay based on solid phase antigen-linked technique (SPLT).…”
Section: Analysesmentioning
confidence: 99%
“…Water total hardness and alkalinity were determined using portable photometers with commercial kits provided by the manufacturer (Wagtecch Portable Photometer 7100, Berkshire, UK). Cortisol was measured using LIAISON Ò cortisol assay kit (DiaSorin Inc., USA) according to Rasooli et al (2009) and Hoseini and Hosseini (2010). The procedure was competitive luminometric assay based on solid phase antigen-linked technique (SPLT).…”
Section: Analysesmentioning
confidence: 99%
“…Tryptophan affects Adrenocorticotropic hormone (ACTH) and cortisol levels, and circulating cortisol is known as the most common indicator of stress in fish, which has been used to evaluate stress-mitigating effects of tryptophan in fish (Lepage et al, 2002;Lepage et al, 2003;Hoseini and Hosseini, 2010;Hoseini et al, 2012;Hosseini and Hoseini, 2013). Effects of tryptophan on fish stress response are situation-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary tryptophan supplementation (0.68-2.72% of diet) has been found to inhibit chronicstress effects on blood cortisol, glucose and immune response in Labeo rohita and Cirrhinus mrigala (Tejpal et al, 2009;Akhtar et al, 2013;Ciji et al, 2013a;Ciji et al, 2013b). The effects of tryptophan on basal and post-stress cortisol show great variability in different fish species; as dietary tryptophan may increase (Lepage et al, 2002;Lepage et al, 2003;Hoseini and Hosseini, 2010) or decrease (Basic et al, 2013a) basal cortisol levels or have no effect on it (Herrero et al, 2007;Hoseini et al, 2012;Wolkers et al, 2012;Basic et al, 2013a;Hosseini and Hoseini, 2013;Martins et al, 2013). In addition, tryptophan may suppress (Lepage et al, 2002;Lepage et al, 2003;Herrero et al, 2007;Hoseini and Hosseini, 2010;Hoseini et al, 2012;Basic et al, 2013b;Hosseini and Hoseini, 2013) or have no effect on post-stress cortisol response (Wolkers et al, 2012;Basic et al, 2013a;Martins et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tryptophan is also reported to be an inefficient precursor of niacin in channel catfish (Ng et al 1997). Recently, Tejpal et al (2008) reported the effects of tryptophan on mitigation in crowding stress response in Cirrhinus mrigala, while tryptophan supplementation enhanced salt water tolerance in common carp (Hoseini and Hosseini 2010).…”
Section: Introductionmentioning
confidence: 99%